The celebrants ebook A novel. - Rowley, Steven (2023)
New York Times Bestseller A TODAY Show #ReadWithJenna Book Club Pick A Big Chill for our times, celebrating decades-long friendships and promises—especially to ourselves—by the bestselling and beloved author of The Guncle. It’s been a minute—or five years—since Jordan Vargas last saw his college friends, and twenty-eight years since their graduation from Berkeley when their adult lives officially began. Now Jordan, Jordy, Naomi, Craig, and Marielle find themselves at the brink of a new decade, with all the responsibilities of adulthood, yet no closer to having their lives figured out. Though not for a lack of trying. Over the years they’ve reunited in Big Sur to honor a decades-old pact to throw each other living “funerals,” celebrations to remind themselves that life is worth living—that their lives mean something, to one another if not to themselves. But this reunion is different. They’re not gathered as they were to bolster Marielle as her marriage crumbled, to lift Naomi after her parents died, or to intervene when Craig pleaded guilty to art fraud. This time, Jordan is sitting on a secret that will upend their pact. A deeply honest tribute to the growing pains of selfhood and the people who keep us going, coupled with Steven Rowley’s signature humor and heart, The Celebrants is a moving tale about the false invincibility of youth and the beautiful ways in which friendship helps us celebrate our lives, even amid the deepest challenges of living.